Analysis of The Dynamics of Moving Cotton in Pipes - Makhmudova Gulshanoy Ozodjon kizi (European Science Publishing, 2023)
The passage of the pipe is the shells (turns), the Sprocket and the separator chambers, where the movement again goes out of balance, the cotton begins to move strongly wavy. Gradually, the trajectory of this movement also fades, when the passage of the pipe comes to the bottom, the movement moves again to an irregular appearance.
Keywords: cotton, pipe, movement, trajectory, balance, critical point, tape device.